Interaction of tomato plants infected by the nematode Meloidogyne javanica on aboveground herbivore Tetranychus urticae and on behaviour of its predator Phytoseiulus macropilis - Morales Murillo, Jose Jahir (2021)
Tritrophic interactions play an important role in the dynamics of arthropods with their hosts. By inducing defenses, plants respond to herbivore attacks, may affect your development. The general objective of this research was to investigate the effect of the nematode Meloidogyne javanica on the performance of the herbivore Tetranychus urticae in tomato plants and, subsequently, whether the nematode infestation affectedthe behavior of its predator Phytoseiulus macropilis. In the first experiment with the herbivore, tomato plants were infested with 2,000 eggs of the nematode M. javanica for a period of 40 days. The immature development, oviposition and preference for choosing plants with or without the nematode were evaluated. A second experiment was carried out with different levels of nematode eggs’ infestation (1,000 and 6,000) atdifferent exposure times (15, 30, and 45 days after infestation). In this experiment, onlyimmature development and survival were evaluated. The spider mite in the first experiment did not show significant differences on immature development and survival,oviposition and preference. For the second experiment, the development of the herbivore T. urticae was affected, with high mortality compared to the control at 30 and45 days after nematode infestation. For the predatory mite, preference experiments evaluated plants attacked simultaneously by the herbivore mite and the nematode or only by the herbivore mite. The predatory mite showed no preference for plants inoculated with the nematode, however, more eggs were found in these plants. The results of this study indicated that with high initial infestation and over time of exposureto the pathogen, the quality of the plant is affected and, consequently, the performanceof aboveground herbivores. The attraction of more predators to plants with nematode infestation increased after 24 hours, which may have varied the number of females that oviposited in this treatment. Thus, it is important to understand the effect on plants when they are attacked by spatially separated organisms above and below ground. In the same way, knowing the importance of direct and indirect interactions in ecological communities it is possible to develop new management techniques andstrategies for crop protection. Keywords: Tritrophic interactions. Root system. Aboveground herbivory. Induced response.